A Collaborative Optimization Approach for Configuring Energy Storage Systems and Scheduling Multi-Type Electric Vehicles Using an Improved Multi-Objective Particle Swarm Optimization Algorithm - Liu, Yirun; Wu, Xiaolong (Processes, 2025)
Energy storage systems (ESS) and electric vehicles (EVs) play a crucial role in facilitating the grid integration of variable wind and solar power. Despite their potential, achieving coordinated operational optimization between ESS and heterogeneous EV fleets to maintain grid stability under high renewable penetration poses a complex technical challenge. To address this, this study develops an integrated optimization framework combining ESS capacity planning with multi-type EV scheduling strategies. For ESS deployment, a tri-objective model balances cost, wind–solar integration, and electricity deficit. A Monte Carlo simulation algorithm is used to simulate different probabilistic models of charging loads for multiple types of EVs, and a bi-objective optimization approach is used for their orderly scheduling. An improved multi-objective particle swarm optimization (IMOPSO) algorithm is proposed to resolve the coupled optimization problem. Case studies reveal that the framework achieves annual cost reductions, enhances the wind–solar integration rate, and minimizes the power deficit in the system.